Fractionality of a given sequence.

Calculus Level 4

Let { a n } n Z 0 = { ( 5 1 2 ) n } \{a_n\}_{n\in\mathbb{Z}_{\geq 0}} = \left\{\left(\frac{\sqrt{5}-1}{2}\right)^n\right\} . Furthermore, let k k be a random non-negative integer. Find the probability that a k a_k can be simplified such that no fractions are involved. Square roots are allowed, however fractions inside square roots are not. Decimal notation is also not allowed.

Examples:

a 0 = ( 5 1 ) 0 2 0 = 1 1 = 1 a_0 = \frac{(\sqrt{5}-1)^0}{2^{0}} = \frac{1}{1} = 1 , which clearly doesn't contain fractions.

a 1 = ( 5 1 ) 1 2 1 = 5 1 2 a_1 = \frac{(\sqrt{5}-1)^1}{2^{1}} = \frac{\sqrt{5}-1}{2} , which can't be simplified without fractions involved.

Hint: First take a look at the first terms of the sequence and try to come up with a recursive formula for it.


The answer is 0.33333333.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Joël Ganesh
Dec 22, 2018

A recursive formula for a n a_n is a n = a n 2 a n 1 , a_n = a_{n-2} - a_{n-1}, with a 0 = 1 , a 1 = 5 1 2 a_0 = 1, a_1 = \frac{\sqrt{5}-1}{2} .

Proof . Let k Z 0 k \in \mathbb{Z}_{\geq 0} . If k { 0 , 1 } k\in \{0, 1\} , the definition of a n a_n already proofs the claim. Therefore, assume k 2 k \geq 2 . It follows that a k = ( 5 1 2 ) k = ( 5 1 2 ) k 1 5 1 2 = ( 5 1 2 ) k 1 5 + 1 2 2 = 5 + 1 2 ( 5 1 2 ) k 1 ( 5 1 2 ) k 1 a_{k} = \left(\frac{\sqrt{5}-1}{2}\right)^k = \left(\frac{\sqrt{5}-1}{2}\right)^{k-1} \cdot \frac{\sqrt{5}-1}{2} = \left(\frac{\sqrt{5}-1}{2}\right)^{k-1} \cdot \frac{\sqrt{5}+1-2}{2} = \frac{\sqrt{5}+1}{2} \left(\frac{\sqrt{5}-1}{2}\right)^{k-1} - \left(\frac{\sqrt{5}-1}{2}\right)^{k-1} \Leftrightarrow a k = ( 5 + 1 ) ( 5 1 ) 4 ( 5 1 2 ) k 2 a k 1 = 5 1 4 a k 2 a k 1 = a k 2 a k 1 , a_k = \frac{(\sqrt{5}+1)(\sqrt{5}-1)}{4} \left(\frac{\sqrt{5}-1}{2}\right)^{k-2} - a_{k-1} = \frac{5-1}{4} a_{k-2} - a_{k-1} = a_{k-2} - a_{k-1}, as expected.

Now note that a k a_{k} can always be written in the form a + b 5 2 \frac{a+b\sqrt{5}}{2} , where a , b Z a,b \in \mathbb{Z} , as a 0 a_0 and a 1 a_1 are in this form and a k a_k is just the (positive) difference between a k 2 a_{k-2} and a k 1 a_{k-1} . In order to get rid of the fraction, both a a and b b must be even numbers.

Furthermore, it can be proven that the difference between an odd number and an even number is odd and that the difference between two odd numbers is always even (see lemma below). With this information, we can see that if a k = a + b 5 2 a_k = \frac{a+b\sqrt{5}}{2} with a , b a, b even numbers and a k + 1 = c + d 5 2 a_{k+1} = \frac{c+d\sqrt{5}}{2} with c , d c,d odd numbers, then a k + 2 = a c + ( b d ) 5 2 = e + f 5 2 a_{k+2} = \frac{a-c+(b-d)\sqrt{5}}{2} = \frac{e+f\sqrt{5}}{2} , where e , f e,f are both odd. We can, applying the same method, also see that in this case a k + 3 = c e + ( d f ) 5 2 = g + h 5 2 a_{k+3} = \frac{c-e+(d-f)\sqrt{5}}{2} = \frac{g+h\sqrt{5}}{2} , where g , h g,h are both even and that a k + 4 = g e + ( h f ) 5 2 = i + j 5 2 a_{k+4} = \frac{g-e+(h-f)\sqrt{5}}{2} = \frac{i+j\sqrt{5}}{2} , where i , j i,j are both odd. Notice that the pattern will now repeat itself, as it has returned to the situation it was in the beginning. The pattern should therefore be like even, odd, odd, even, odd, odd, ... Also, notice that a 0 a_0 and a 1 a_1 have the properties which a k a_k and a k + 1 a_{k+1} have, respectively.

As stated earlier, to get rid of the fraction, we need to have for arbitrarily chosen l Z 0 l \in \mathbb{Z}_{\geq 0} that a l = l 1 + l 2 5 2 a_l = \frac{l_1 + l_2\sqrt{5}}{2} , where l 1 , l 2 l_1, l_2 are both even. With the pattern even, odd, odd, even, odd, odd, ..., it should be clear that the probability of a k a_k being fractionless after simplifying is 1 3 \boxed{\frac{1}{3}} .

Lemma: (1) The difference between an odd number and an even number is odd and (2) the difference between two odd numbers is even.

Proof . We first proof (1). An even number can be written as 2 n 2n , where n Z n \in \mathbb{Z} and an odd number can be written as 2 m + 1 2m+1 , where m Z m \in \mathbb{Z} . Therefore their difference can be written as 2 m + 1 2 n = 2 ( m n ) + 1 = 2 k + 1 2m+1-2n = 2(m-n)+1 = 2k+1 , where k = m n k = m-n . The difference between two integers is an integer, so k Z k \in \mathbb{Z} and we conclude that the difference between an odd number and an even number is odd.

Now we proof (2). We can write the two odd numbers as 2 n + 1 2n+1 and 2 m + 1 2m+1 respectively, where n , m Z n,m \in \mathbb{Z} . Their difference therefore is 2 m + 1 ( 2 n + 1 ) = 2 m 2 n = 2 ( m n ) = 2 k 2m+1-(2n+1) = 2m - 2n = 2(m-n) = 2k , where k = m n k = m-n . Again, the difference between two integers is an integer, so k Z k \in \mathbb{Z} and we conclude that the difference between two odd numbers is even.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...